The consistency of export and agricultural policies in Egypt - Sultan, Nourhan Ahmed (AUC Knowledge Fountain, 2020)
This study examines Egypt's agricultural policies, trade policies and their synergies or inconsistence. The analysis of the agricultural sector and its performance over time identifies constraints to increasing production and exports. It also examines the key role of trade in encouraging inclusive agricultural development. After a review of current trends in the agricultural sector and trade policies, the study elaborates on the main policies regulating the current agricultural export sector. It also explores the factors influencing the water scarcity problem and what could mitigate it. This qualitative research attempts to illustrate to what extent the Egyptian agricultural export sector policies are effective, consistent, and reliable. Findings demonstrate that there are contradictions in the guiding principles of these policies, and rectification is required to maintain better results in this sector. In addition, the high price of irrigation water and the government policies of water conservation are not met with policies to encourage introducing water saving technologies to support producers. The study concludes by recommending policy changes to improve trade performance and agricultural production, and to create more consistency with the export policies.